2020
DOI: 10.1111/rda.13841
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial expression of key genes related to fertility in repeat breeder and non‐repeat breeder cows

Abstract: The aim of the present study was to compare the endometrial gene expression of epidermal growth factor receptor (EGFR), nodal growth differentiation factor (NODAL), prostaglandin-endoperoxide synthase 2 (PTGS2), oestrogen receptor 1 (ESR1) and progesterone receptor (PGR) in repeat breeder cows (RBC) and non-RBC during diestrus. Endometrial samples were collected by cytobrush technique and stored in RNA stabilizing solution at −20°C until RT-qPCR analysis. Differences in endometrial mRNA expression of selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…PPP2R2A has been demonstrated to promote implantation of embryos in vitro and in vivo, respectively, via Ppp2r2a knockout mice and function gain and loss assays of PPP2R2A in sheep ESCs [60,61]. PTGS2 was reported to be more abundant in repeat breeder cows (RBC) than in non-RBC and is involved in the regulation of some protein markers in the in vitro endometrial receptivity of endometrial epithelial cells (EEC) in dairy goats [62,63]. Hiraoka et al reported that the collaborative regulation of uterine receptivity and embryo attachment involves distinct pathways utilized by epithelial and stromal STAT3, resulting in synergistic effects [64].…”
Section: Discussionmentioning
confidence: 99%
“…PPP2R2A has been demonstrated to promote implantation of embryos in vitro and in vivo, respectively, via Ppp2r2a knockout mice and function gain and loss assays of PPP2R2A in sheep ESCs [60,61]. PTGS2 was reported to be more abundant in repeat breeder cows (RBC) than in non-RBC and is involved in the regulation of some protein markers in the in vitro endometrial receptivity of endometrial epithelial cells (EEC) in dairy goats [62,63]. Hiraoka et al reported that the collaborative regulation of uterine receptivity and embryo attachment involves distinct pathways utilized by epithelial and stromal STAT3, resulting in synergistic effects [64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GAPDH and HPRT1 (along with SDHA ) belonged to the least stably expressed RGs in bovine ovaries 12 . Nonetheless, GAPDH continues to be used as the internal control in many gene expression studies of bovine reproductive tissues 33 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone concentration in plasma was measured by chemiluminescence (Immunoanalyzer Elecsys and Cobas e, Roche; Jaureguiberry et al, 2020;Madoz et al, 2021). The assay's precision was determined by including control samples with low (1 ng/mL) and high (7 ng/mL) P4 concentrations by duplicates at the beginning and the end of the assay.…”
Section: Determination Of P4 Concentrationsmentioning
confidence: 99%